Moderated by personal perception: The preventive relationship between home HIIT dance and depression during the COVID-19 pandemic in China - Yifan Hu; Yifan Hu; KwanJung Son; Zheng Yang; Yufei Mao (Frontiers Media S.A., 2023)
IntroductionLockdowns during the COVID-19 pandemic were believed to greatly increase the risk of depression among isolated residents in both China and in Western countries. How to effectively reduce this risk has become one of the key issues in the field of public mental health.MethodsThe present study seeks to examine the preventive relationship between doing home HIIT dance-which became popular during Shanghai's COVID-19 lockdown in 2022-and depression, and how such a preventive relationship has been mediated by different personal perception factors using an online survey with 528 samples.ResultsThe preventive relationship between doing home HIIT dance and depression was differently mediated by residents' personal perception factors, such as perceived benefits, severity, and self-efficacy, based on the health belief model.DiscussionThese results deepen the research on the psychological effects of doing home HIIT dance on preventing depression, especially in the COVID-19 lockdown period, emphasizing the possible moderation effects of different self-perception factors.